2009
DOI: 10.1007/s10803-009-0730-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety in Cornelia de Lange Syndrome

Abstract: In this study we assessed the behavioral presentation of social anxiety in Cornelia de Lange syndrome (CdLS) using a contrast group of Cri du Chat syndrome (CdCS).Behaviors indicative of social anxiety were recorded in twelve children with CdLS (mean age = 11.00; SD = 5.15) and twelve children with CdCS (8.20; SD = 2.86) during social interaction. Lag sequential analysis revealed that participants with CdLS were significantly more likely to evidence behavior indicative of anxiety in close temporal proximity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 37 publications
1
49
1
Order By: Relevance
“…Individuals with profound ID could fulfil a task if their processing speed was considered during assessments, for example through prolonged offering of visual task‐stimuli. We noticed that almost all participants quickly built up routines in their actions, which might be brought on by anxiety (Richards, Moss, O'Farrell, Kaur, & Oliver, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with profound ID could fulfil a task if their processing speed was considered during assessments, for example through prolonged offering of visual task‐stimuli. We noticed that almost all participants quickly built up routines in their actions, which might be brought on by anxiety (Richards, Moss, O'Farrell, Kaur, & Oliver, ).…”
Section: Discussionmentioning
confidence: 99%
“…Less impaired eye contact in the CdLS group is particularly interesting and is consistent with Nelson (2010) who described frequent and prolonged eye gaze in CdLS compared to individuals with Down syndrome. Increased anxiety in CdLS is also consistent with previous reports of increased levels of social anxiety in the syndrome (Collis et al., 2006; Goodban, 1993; Moss et al., 2008b; Richards et al., 2009) and suggests that the nature (and possibly the underlying causes) of social impairments in CdLS may be different to those observed in ASD. Taken together, these findings suggest that individuals with CdLS have motivation or desire to engage with others (indicated by frequent eye contact), combined with a lack of skill/ability to engage (indicated by social and communication impairments) and anxiety relating to social encounters (indicated by the higher rates of anxiety).…”
Section: Discussionmentioning
confidence: 99%
“…When validation of diagnosis was not defined and authors could not be reached for a definitive answer, papers were excluded. Three studies that reported confirmed diagnosis based on parent reports were included . Risk of bias was reduced by removing duplicates.…”
Section: Methodsmentioning
confidence: 99%